If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + (x + -25) = 523 Reorder the terms: x + (-25 + x) = 523 Remove parenthesis around (-25 + x) x + -25 + x = 523 Reorder the terms: -25 + x + x = 523 Combine like terms: x + x = 2x -25 + 2x = 523 Solving -25 + 2x = 523 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '25' to each side of the equation. -25 + 25 + 2x = 523 + 25 Combine like terms: -25 + 25 = 0 0 + 2x = 523 + 25 2x = 523 + 25 Combine like terms: 523 + 25 = 548 2x = 548 Divide each side by '2'. x = 274 Simplifying x = 274
| x^2-6x+8=8 | | 125-5x=2+20 | | -5d+1+4/5d=-10/11 | | -5b=20/7 | | -5b=-15/7 | | -5b-9=-37/3 | | -5b-8-2/3b=-80/27 | | -5b-7/9=-142/9 | | -5b-6/7=-74/21+1/3b | | -5b-6=-16 | | -5b-6-7b=-30 | | -5b-4/5=-157/40 | | -5b-3=-43 | | -5b+7/10=-b-153/10 | | -5b+7+2b=38/5 | | -5b+5/6=-325/6 | | -5b+5=25 | | -5b+1=-26/9 | | -5b+1+2b=-16/11 | | -5a=-5 | | -5a-8=-21/2 | | -5a-6+2a=9 | | -5a-5/8+4/7a=-547/280 | | -5a-5=-1 | | -5a-4/7=34/63 | | -5a-2/9-a=-118/45 | | -5a-2/3=-17/3 | | -5a-1/2=-3 | | -5a-1=26/9 | | -5a+9=33+a | | -5a+9=-41 | | -5a+8=34/3 |